Kekerasan terhadap perempuan dalam wacana tafsir keagamaan di Indonesia perspektif Islam - Marzuki Marzuki (Jurnal Civics: Media Kajian Kewarganegaraan, 2006)
This is a content analysis research that examines the contents of the books of fiqh that have the potential existence of gender violence; especially a book entitled Vqud al-Lujjain fi alBayani Huquq al-Zaujain; a work of Muhammad ibn Umar al-Nawawi al-Banteni; in gender equality and justice perspective. This study shows that gender violence among the Muslim community,particularly in Indonesia, was much influenced by the circulation of the books of fiqh that have the potential gender bias and have an impact on religious thought and behavior. Among of causalfactors is the influence cfinterpretations of the scholars whose interpretations are characterized by a partial, not comprehensive, literal (textual), not contextual, and heavily itifluenced by local culture. As a result, the understanding is less consistent with the principles of al-Qurran that stressed equality,justice, and .freedom. The eJfortneed to be done is reconstruction and reformulation of the books offiqh.